Pelatihan Pemanfaatan Wordwall dan Canva Berbasis Kearifan Lokal dalam Pembelajaran Bahasa Indonesia di SMKN 2 Gowa - Syahruddin Syahruddin; M. Agus; Hasriani Hasriani; Rasulong, Ismail; Yusuf, Muhammad; Kahar Kahar (Jurnal Pengabdian Bersama Masyarakat Indonesia, 2026)
This community service program addressed the need for more interactive and culturally contextual Indonesian language learning at SMKN 2 Gowa. The activity aimed to strengthen teachers' and students' capacity to use Wordwall and Canva while integrating local wisdom from Gowa into learning materials. The program was implemented through needs identification, preparation of learning content, demonstrations, guided practice, mentoring, product review, and reflection. Wordwall was used to develop interactive exercises for identifying the structure and linguistic features of an observation report concerning Balla Lompoa, whereas Canva was used to produce digital comics and visual materials for anecdotal texts and social criticism. The implementation showed that participants could use the basic features of both applications, transform local cultural content into digital learning resources, and participate more actively in classroom activities. The culturally familiar content made the tasks more meaningful and encouraged discussion about local heritage. Constraints included unequal digital skills, limited devices, internet instability, and the time required to prepare relevant cultural content. Step-by-step mentoring, peer support, and reusable templates helped reduce these barriers. The program indicates that combining digital media training with local wisdom can strengthen digital literacy, creativity, cultural appreciation, and contextual Indonesian language learning.